Total Culturable Microbial Diversity of Food Contact Surfaces in Poultry and Fish Processing Industries After the Pre-Operational Cleaning Process - Luiz Gustavo Bach; Gabriela Zarpelon Anhalt Braga; Márcia Cristina Bedutti; Layza Mylena Pardinho Dias; Emanoelli Aparecida Rodrigues dos Santos; Leonardo Ereno Tadielo; Evelyn Cristine da Silva; Jhennifer Arruda Schmiedt; Virgínia Farias Alves; Elaine Cristina Pereira De Martinis; Fábio Sossai Possebon; Vinicius Cunha Barcellos; et al. (Foods, 2025)
This study assessed the viable and culturable microbial diversity that remained on equipment surfaces after hygiene procedures in Brazilian poultry and fish slaughterhouses. Food-contact surface samples were collected using sterile swabs in poultry (n = 50) and fish (Oreochromis niloticus, n = 50) slaughterhouses. The swab samples were used to prepare culture plates to recover viable and culturable cells. The grown plates were washed, and the total DNA of the cell suspension was extracted with a commercial kit. Sequencing of the total DNA extracted from cultures was targeted at the V3 and V4 regions of the 16S rRNA. DNA reads were analyzed by QIIME2 software, with results expressed in relative frequency (%RF). Alpha and beta diversity indexes were analyzed considering the spots of sample collection, type of industry, surfaces (smooth or modular), and materials (polypropylene, stainless steel, or polyurethane). The results showed that in the poultry slaughterhouse, the most abundant genera were Acinetobacter (27.4%), Staphylococcus (7.7%), and Pseudomonas (5.3%), while for the fish slaughterhouse, there was a higher abundance of Staphylococcus (27.7%), Acinetobacter (17.2%), and Bacillus (12.5%). Surface characteristics influenced the microbial diversity, with Acinetobacter spp. dominating modular surfaces and Staphylococcus spp. prevailing on smooth surfaces. The results obtained indicate there is an important resident microbiota that persists even after hygiene processes, and surface-specific cleaning strategies should be developed.